INTERPERSONAL MEANING CONSTRUCTION IN THE OPRAH WINFREY TALK SHOW - Udi Samanhudi; Ari Arifin D (University of Muhammadiyah Purwokerto, 2010)
This article explores the variation of interpersonal meanings construction in the Oprah Winfrey talk show. It focuses on how Oprah Winfrey, the host of the program, constructs meanings interpersonally in the progress of her conversations. Using systemic functional grammar, a transcript of the Oprah dialogues was analyzed through identification of clause mood structure and speech function. The patterns of mood structures and speech functions, the use of mood elements, like subject, finite, complement, adjuncts and modals were investigated. In analyzing the data, the researchers also explore the use of non verbal communication features by Oprah during her talk. This is used to enrich interpretations towards the data being analyzed. The results suggest that Oprah uses her time asking questions to her guest/s. Oprah uses various ways of digging more information by especially employing those probing and rhetorical questions. The first one is indicated by confirming, clarifying, exploring points and exclamation and the second is done by gaining agreement, cross questioning and reviewing questions. Another finding is the fact that she is also very good at integrating non verbal language features in her talk such as facial expressions and tones in order to make meanings easy to transfer.